MEDIA PEMBELAJARAN SEBAGAI MOTOR PENGGERAK PENINGKATAN HASIL BELAJAR IPA DI SEKOLAH DASAR - Soi'mah, Hadiyatus; Prayogo, Muhammad Suwignyo; Azizah, Wahyu Lu’atul; Lestari, Mujiah Indah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The low achievement of science learning outcomes at the elementary school level indicates that students continue to face difficulties in understanding abstract subject matter. This situation underscores the need for innovation in the use of instructional media so that the teaching and learning process can become more concrete, engaging, and easier for students to understand. This study is intended to examine the extent to which the use of instructional media is effective in improving science learning outcomes. The investigation was conducted by combining a meta-analysis of five classroom action research articles with direct observation of sixth-grade students at SDN Tempurejo 01. Data collection was carried out through a review of scientific journals relevant to instructional media and the improvement of science learning outcomes, as well as through observation of learning activities utilizing concrete media in the form of miniature models of the Earth, Moon, and Sun. The findings indicate that the continuous use of instructional media is able to enhance students’ understanding of science concepts and promote active student engagement, as reflected in both previous research findings and field observations. Based on these overall findings, it can be concluded that the utilization of instructional media plays a strategic role in fostering more active, enjoyable, and meaningful science learning experiences for elementary school students. ABSTRAK Rendahnya capaian hasil belajar IPA di tingkat sekolah dasar mengindikasikan bahwa peserta didik masih menghadapi hambatan dalam memahami materi yang bersifat abstrak. Situasi tersebut menegaskan perlunya pembaruan dalam pemanfaatan media pembelajaran agar kegiatan belajar mengajar dapat berlangsung secara lebih konkret, menarik, serta mudah dipahami oleh siswa. Penelitian ini diarahkan untuk mengkaji sejauh mana efektivitas penggunaan media pembelajaran dalam meningkatkan hasil belajar IPA. Kajian dilakukan dengan memadukan meta-analisis terhadap lima artikel penelitian tindakan kelas dan observasi langsung terhadap siswa kelas VI di SDN Tempurejo 01. Pengumpulan data dilaksanakan melalui telaah jurnal ilmiah yang relevan dengan topik media pembelajaran dan peningkatan hasil belajar IPA, serta melalui pengamatan proses pembelajaran yang memanfaatkan media konkret berupa miniatur bumi, bulan, dan matahari. Hasil penelitian memperlihatkan bahwa penggunaan media pembelajaran secara berkelanjutan mampu meningkatkan pemahaman konsep IPA dan mendorong keterlibatan aktif siswa, baik berdasarkan temuan penelitian sebelumnya maupun hasil observasi di lapangan. Berdasarkan keseluruhan temuan tersebut, dapat disimpulkan bahwa pemanfaatan media pembelajaran memiliki peran strategis dalam mewujudkan pembelajaran IPA yang lebih aktif, menyenangkan, dan bermakna bagi siswa sekolah dasar.